Genes for a microaerobically induced oxidase complex in Bradyrhizobium japonicum are essential for a nitrogen-fixing endosymbiosis. - Preisig, O (1993)
We report the discovery of a Bradyrhizobium japonicum gene cluster (fixNOQP) in which mutations resulted in defective soybean root-nodule bacteroid development and symbiotic nitrogen fixation. The predicted, DNA-derived protein sequences suggested that FixN is a heme b and copper-binding oxidase subunit, FixO a monoheme cytochrome c, FixQ a polypeptide of 54 amino acids, and FixP a diheme cytochrome c and that they are all membrane-bound. The isolation and analysis of membrane proteins from B. japonicum wild-type and mutant cells revealed two c-type cytochromes of 28 and 32 kDa as the likely products of the fixO and fixP genes and showed that both were synthesized only under oxygen-limited growth conditions. Furthermore, fixN insertion and fixNO deletion mutants grown microaerobically or anaerobically (with nitrate) exhibited a strong decrease in whole-cell oxidase activity as compared with the wild type. The data suggest that the fixNOQP gene products are induced at low oxygen concentrations and constitute a member of the bacterial heme/copper cytochrome oxidase superfamily. The described features are compatible with the postulate that this oxidase complex is specifically required to support bacterial respiration in endosymbiosis.